Melancholia.: Come smontare l’inizio (PHILM. Rivista di filosofia e cinema, 2024)
Everything is already written in the beginning. The rest will be nothing but repetition. This is how Lars Von Trier’s Melancholia opens, revealing the secret of melancholy and the shadow it casts over life. The stark alternative it offers us – between the imaginary paranoia and the tragic disenchantment of science – seems capable of grasping the question at which the time we live is suspended: Melancholia is a film about the failure of knowledge and the emergence of the real. However, after the absolute beginning that Lars von Trier captures in his film’s overture, between the globe and the planet about to strike it, the film opens up an additional time, that of waiting just when there is no time left.